OptoRibo-seq for spatiotemporally resolved mapping of the local protein translatome - Ruixuan Wang; Ruixiang Wang; Wentao Wang; Yanjun Liu; Fu Zheng; Huixin Luo; Peng R. Chen; Peng Zou (Proceedings of the National Academy of Sciences, 2026)
Localized protein translation occurs in numerous subcellular compartments and regulates diverse biological processes by rapidly changing protein compositions in response to subcellular needs. Existing assays for subcellular local translation either require physical isolation, which is prone to contamination and loss of material, or imaging-based readout, which is often hampered with low throughput. In this study, we report the development of the optoRibo-seq method that features photoactivatable enzyme-mediated proximity labeling of ribosomes in genetically specified subcellular locations. We demonstrate the spatial specificity of optoRibo-seq at the endoplasmic reticulum (ER) membrane, with a temporal resolution of 1 min. In cells undergoing chemically induced ER stress, optoRibo-seq allowed mapping of the dynamic changes in the ER-proximal translatome, identifying transcripts involved in protein folding and targeting. Our strategy provides a general platform for spatiotemporally resolved profiling of subcellular protein translation.